STay tunEd: mutational analysis of the HvSTE1 gene in barley provides insight into the balance between semi-dwarfism and maintenance of grain size in brassinosteroid biosynthesis-dependent manner - Zolkiewicz, Karolina; Oklestkova, Jana; Chmielewska, Beata; Gruszka, Damian (Frontiers in Plant Science, 2025)
Brassinosteroids (BRs) are steroid phytohormones which regulate various physiological and developmental processes throughout plant life cycle. The BR biosynthesis has been studied mainly in the dicot model species - Arabidopsis thaliana. However, our current understanding of the BR biosynthesis and its regulation in other species, including cereal crops, is limited. Functions of enzymes which catalyze early stages of the BR biosynthesis in cereals remain poorly understood. Moreover, mechanisms regulating expression of genes encoding these enzymes remain obscure. One of the genes which participate in the early stages of the BR biosynthesis in Arabidopsis is STE1 (STEROL DESATURASE1). However, detailed functional analyses of this gene and its promoter region have not been performed. The aim of this study was to identify and functionally analyze the STE1 gene in barley (Hordeum vulgare) which is an important cereal crop. The functional analysis was carried out with the application of TILLING (Targeting Induced Local Lesions IN Genomes) approach. Six mutations were identified within the 1st exon (including three located in the 5’UTR region) and one missense mutation was identified in the 2nd exon of HvSTE1. Effects of the identified alleles on the HvSTE1 gene expression, sequence of the encoded enzyme variants, BR accumulation, as well as on stature, agronomic traits, and reproduction of the identified mutants were characterized. Homozygous mutants carrying two alleles (hvste1.b and hvste1.o) displayed reduced plant height and defects in the BR accumulation. The HvSTE1 expression was considerably decreased in the 3rd internode of the hvste1.b mutant. Interestingly, the hvste1.b mutant plants showed semi-dwarf phenotype without any negative effect on crucial agronomic traits, such as tiller number, spike length, and grain weight. Moreover, weight of grains produced by the hvste1.b mutant was slightly (5%) higher when compared with the reference cultivar. The results of this study provided a novel insight into the function of the HvSTE1 gene in the BR biosynthesis-dependent regulation of architecture and reproduction of barley. Moreover, the hvste1.b allele allows for achieving a balance between the favorable alteration in plant architecture (semi-dwarfism) and maintenance (slight improvement) of grain weight in this species.